P91 Socio-economic inequalities in childhood wheeze and atopy: longitudinal findings from the Southampton Women's Survey. (13th September 2016) - Pearce, A; Pike, K; Taylor-Robinson, D; Baird, J; Godfrey, K; Lucas, J; Rougeaux, E; Law, C; Inskip, H
Abstract : Background: Wheeze is one of the most common chronic conditions in childhood. Understanding its social risk factors is important for prevention. However, studies examining inequalities in wheeze have shown inconclusive results. This is potentially due to the complexities of differentiating between wheezing illnesses, which have different underlying causes, many associated with socio-economic disadvantage but some with advantage (e.g. atopy). We therefore investigated inequalities in typologies of wheeze and atopy, using longitudinal data and objective atopic status. Methods: We used data from the Southampton Women's Survey (SWS), a population-based study of non-pregnant 20–34 year (y) old women, resident in Southampton (UK), 1998–2002. Offspring, born 1998–2007, were followed through childhood. Information included maternal-reported wheeze (6 months (m), 12 m, 2 y, 3 y, 6 y), and skin prick tests for atopic sensitisation (12 m, 3 y, 6 y). Longitudinal typologies of wheeze and atopy were created using latent class analysis in children with complete data at 6 y ( n = 1258; 40% of original recruits, 69% of those seen at 6 y). Two- to seven-class measures were assessed based on model fit and interpretability. Children were assigned to the class to which they had the highest probability of belonging. Socio-economic differences in wheeze were examined with relative risk ratios (RRRs [95% confidence intervals]), according to maternal highest academic qualifications (GCSEs/None; A-Levels; Diploma/Degree). Sensitivity analyses included: weighting analyses to account for uncertainty of class assignment, using an alternative measure of socio-economic circumstances (maternal occupation), and imputing missing data. Analyses were conducted in Stata 13.0 (and 'SAS PROC LCA' plug-in). Results: Five classes of wheeze and atopy emerged: 'No Wheeze, No Atopy' (53%), 'Non-atopic Early Wheeze' (15%); 'Non-atopic Remitting Wheeze' (16%); 'Atopic Increasing/Persistent Wheeze' (7%); 'Atopy Only' (10%). Compared with children whose mothers had GCSEs/None, those whose mothers had a Diploma/Degree were less likely to experience 'Non-atopic Remitting Wheeze' (RRR = 0.55 [0.37–0.82]), no less likely to experience 'Non-atopic Early Wheeze' (1.13 [0.77–1.70]), and more likely to have 'Atopy Only' (1.79 [1.12–2.89]). In analyses restricted to atopic children, those whose mothers had a Diploma/Degree were less likely to develop 'Atopic Increasing/Persistent Wheeze' (0.49 [0.24–0.98]). There were few differences between those with A-levels and GCSEs/None. Sensitivity analyses produced similar patterns. Conclusion: Children of mothers with lower educational qualifications were more likely to experience non-atopic remitting wheeze and, if they had atopy, to develop persistent wheeze. These findings require replication in larger samples and beyond the age of 6 y (including in the SWS). Future research to explain these inequalities will help shape interventions.